An Analysis of Indonesian and English Code-Mixing in the YouTube Comments Section of Gita Savitri Devi - Aini, Nazila Qorirol (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the phenomenon of code-mixing, namely the use of both English and Indonesian, employed by social media users, particularly viewers or fans of the influencer Gita Savitri Devi in several videos uploaded to YouTube. In today’s digital era, the use of English in everyday conversations has become a widespread trend among Indonesian society and is considered a substantial phenomenon. This research employs a qualitative descriptive method to analyze the data. The data were collected through an observation technique using 20 screenshots of comments written by viewers or fans on videos uploaded by Gita Savitri that contained a mixture of English and Indonesian. The main theory used in this study is proposed by Shana Poplack, who classifies code-switching into three main types: tag switching, inter-sentential switching, and intra-sentential switching. The results of the study from 20 samples showed that 18 were categorized as intra-sentential switching. This indicates that intra-sentential switching is the most dominant type used, driven by the need for more efficient expression and the influence of global digital culture. This study provides an overview of how code-mixing functions as a communication tool and a form of identity expression among the younger generation.